Domain-averaged Fermi hole and domain-restricted reduced density matrices: A critical comparison - Alcoba, Diego Ricardo (2011)
The knowledge of the properties and the applicability of domain-restricted matrices has provided important advances in the description of molecular electronic distributions. In this work, we perform a critical comparison between two different methods: the domain-averaged Fermi hole (DAFH) approach and the domain-restricted first-order reduced density matrix (DRRDM) one, focusing our study on both physical and mathematical points of view. Our results permit to show that both methods have a markedly different behavior at correlated wave function level: the DAFH approach provides information related with electron cloud localization and populations while the DRRDM is a true density matrix. To exemplify the theoretical discussion, we present a numerical test example and a simple analytical model that show such features. © 2010 Wiley Periodicals, Inc.